Ground water regimes containing country rock minerals in Southern Kuzbass (case study: Narysk-Ostashkin) - Domrocheva, E.; Lepokurova, Olesya Evgenyevna (IOP Publishing, 2016)
The paper describes the calculation results revealing groundwater in equilibrium to carbonates and aluminosilicate minerals of country rocks in Narysk-Ostashkinsk area. It was proved that groundwater is in nonequilibrium to primary (endogenous) minerals in which they dissolve, however are in equilibrium to clays and carbonates which precipitate in the groundwater. The groundwater composition varies.
Keywords: подземные воды; минералы; Кузбасс; карбонаты; алюмосиликатные материалы; полезные ископаемые; грунтовые воды; глины